2022
DOI: 10.3390/ma15062304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Subgrade Material of Calcium Silicate Slag

Abstract: Calcium silicate slag (CSS) is used as a secondary solid waste produced by aluminum extraction technology from high alumina fly ash, and its resource utilization has always been a key issue to be solved. In this study, CSS was used to replace a portion of fly ash (FA) to prepare a new inorganic binder stabilized material for road base. The unconfined compressive strength (UCS), phase composition, microstructure, durability and performance index of the base of the test section of the CSS pavement base material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results showed that with an increase in the reaction temperature, a finer particle size of magnesium slag, an increase in the liquid-solid ratio and an increase in the NH 4 Cl mass fraction, the leaching effect of calcium will be enhanced. The leaching rate of calcium in magnesium slag was found to reach 77.01% under the conditions including a NH 4 Cl mass fraction of 30%, leaching temperature of 90 • C, liquid-solid ratio of 10 and leaching time of 4 h. Kan Hong et al [130] used calcium silicate slag as a raw material to recover tungsten and molybdenum with the alkali roasting-ball milling leaching process. The experiment showed that the process has strong applicability, and the recovery rate of tungsten and molybdenum can reach the ideal level when dealing with the solid solution slag of calcium silicate smelting with tungsten and molybdenum.…”
Section: Comparison Of Parameters In the Different Magnesium Smelting...mentioning
confidence: 99%
“…The results showed that with an increase in the reaction temperature, a finer particle size of magnesium slag, an increase in the liquid-solid ratio and an increase in the NH 4 Cl mass fraction, the leaching effect of calcium will be enhanced. The leaching rate of calcium in magnesium slag was found to reach 77.01% under the conditions including a NH 4 Cl mass fraction of 30%, leaching temperature of 90 • C, liquid-solid ratio of 10 and leaching time of 4 h. Kan Hong et al [130] used calcium silicate slag as a raw material to recover tungsten and molybdenum with the alkali roasting-ball milling leaching process. The experiment showed that the process has strong applicability, and the recovery rate of tungsten and molybdenum can reach the ideal level when dealing with the solid solution slag of calcium silicate smelting with tungsten and molybdenum.…”
Section: Comparison Of Parameters In the Different Magnesium Smelting...mentioning
confidence: 99%